Rediscovery of the rare Atractus bocki, with assessment of the taxonomic status of Atractus canedii (Serpentes: Colubridae: Dipsadinae) - Passos, Paulo (2009)
Atractus bocki was described based on a single specimen from the Cochabamba region in Bolivia, and since its original description, there have been no further records for the species. During the examination of Argentinean and Bolivian collections, we found four additional specimens of this poorly known snake. In this paper, we describe these individuals and report new data on meristic and morphometric variation for A. bocki. We also evaluate the taxonomic status of Atractus canedii and propose its synonymy with A. bocki.